Stored blood transfusion induces transient pulmonary arterial hypertension without impairing coagulation in an ovine model of nontraumatic haemorrhage. Issue 2 (5th March 2013) - Fung, Y. L.; Tung, J. P.; Foley, S. R.; Simonova, G.; Thom, O.; Staib, A.; Collier, J.; Dunster, K. R.; Solano, C.; Shekar, K.; Chew, M. S.; Fraser, J. F.
<x xml:space="preserve">Abstract</x> Background and Objectives Transfusion of blood products in particular older products is associated with patient morbidity. Previously, we demonstrated a higher incidence of acute lung injury in lipopolysaccharide‐treated sheep transfused with stored blood products. As transfusion following haemorrhage is more common, we aimed to determine whether a 'first hit' of isolated haemorrhage would precipitate similar detrimental effects following transfusion and also disrupt haemostasis. Materials and Methods Anaesthetized sheep had 33% of their total blood volume collected into Leukotrap bags (Pall Medical), which were processed into packed red blood cells and cross‐matched for transfusion into other sheep. After 30 mins, the sheep were resuscitated with either: fresh (<5 days old) or stored (35–42 days old) ovine blood followed by 4% albumin to replacement volume, albumin alone or normal saline alone and monitored for 4 h. Results The first hit of haemorrhage precipitated substantial decreases in mean arterial pressure however haemostasis was preserved. Transfusion of stored ovine blood induced (1) transient pulmonary arterial hypertension but no oedema and (2) reduced fibrinogen levels more than fresh blood, but neither induced coagulopathy. Thus, transfusion of stored blood affected pulmonary function even in the absence of overt organ injury. Conclusion The fact that stored blood transfusions: (1) did not induce acute lung injury in contrast to previous lipopolysaccharide‐primed animal models identifies the 'first hit' as an important determinant of the severity of transfusion‐mediated injury; (2) impaired pulmonary dynamics verifies the sensitivity and vulnerability of the pulmonary system to injury.